(untitled) (Research, Society and Development, 2022)
Objective: To explore the conception of nursing professionals in relation to work experiences in times of the COVID-19 pandemic. Methods: This is a qualitative, descriptive, exploratory study carried out in 3 cities in northwest Paraná, with 34 nursing professionals who worked on the front line against the coronavirus. Data were collected using an electronic form. Results: With the data collected, it is observed that most nursing professionals took the vaccine against the SARS-CoV-2 virus of COVID-19 and that PPE was made available at their workplace, although they were lacking at some point. Most did not receive any type of training, lectures or training, which, added to other findings, caused and worsened states of stress, fears, anxiety and exhaustion, as well as triggering diseases. Conclusion: It is concluded that the pandemic had a direct impact on the mental and physical health of nursing professionals, regarding fear, anxiety, stress, physical and mental fatigue.